Collecting Duct Carcinoma in the Kidneys: A Rare Case Report - Aini, Julpa Nurul; Noza Hilbertina; Pamelia Mayorita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Collecting duct carcinoma (CDC) is one of the rare pathological subtypes of renal cell carcinoma, with high malignancy and poor prognosis. Pathological examination is the gold standard in confirming the diagnosis of CDC. CDC is described as a tumor that has a tubulopapillary architecture and forms a hobnail pattern along the glandular tube. Case presentation: A 56-year-old woman with the main complaint of a lump in the right abdomen for 1.5 months before entering the hospital. The lump in the stomach is getting bigger, complaints are accompanied by intermittent pain, nausea, vomiting, body feeling weak, and decreased appetite. The patient then underwent a CT-Scan examination of the abdomen and concluded that fluid/water was found next to the right kidney, and a hypodense lesion appeared in segment 6 of the right lobe of the liver. Histopathological examination of large tissue shows pieces of kidney tissue with a connective tissue capsule on the outside containing glomeruli and tubules lined by cuboidal epithelium as well as a proliferation of tumor cells that grow infiltratively in the connective tissue stroma which is partly desmoplastic and fatty tissue between the glomeruli and tubules. Tumor cells are arranged to form tubulopapillary and tubulocystic structures. These cells with pleomorphic nuclei, some hyperchromatic, some vesicular, coarse chromatin, clear nuclei, and atypical mitoses can be found and tumor cell embolism in the blood vessels and perineural invasion can be seen. There were spots and clusters of lymphocytes and plasma cells as well as areas of bleeding and necrosis. Conclusion: The patient was diagnosed with collecting duct carcinoma (CDC).